STATE SUPPORT FOR YOUTH ENTREPRENEURSHIP UNDER MARTIAL LAW (Innovative professional education, 2024)
The article highlights the peculiarities of youth entrepreneurship in Ukraine and state support for students under martial law. Youth entrepreneurship is seen as a key factor in the economic recovery of post-war Ukraine. Various initiatives aimed at supporting youthentrepreneurship are discussed, involving both government agencies and non-governmental organisations. In addition, the potential for young entrepreneurs to continuously update their skills and knowledge to meet modern standards is highlighted.
Keywords: youth entrepreneurship, state support, student youth, economic recovery, martial law